Desenvolvimento e capacidades estatais : um estudo de caso dos pequenos municípios da região de São Carlos - Moretti, Daniel Profiti (2015)
The object of this work was to develop a panel about the installed institutional capacity in the municipalities of Ribeirão Bonito and Dourado – State of São Paulo, while characterized as small municipalities around an important country development center, the city of São Carlos. Therefore, it was made an analysis starting from the polysemic concept of Development, dissociating it from a mere economic growth, but adding to it the New-Developmentalism characteristics experienced in Brazil from the XXI century forth related to income distribution policies and popular empowerment. After that, it explains the difference between this phase and the nationaldevelopmentalism era of the second half of the XX century, when the logic of development was mostly an economic subject. Leather then go to an analysis of the characteristics of the state capacities required to this State in order to understand how this can promote the development of remote or small communities and devoid of endogenous possibilities for social transformation. It concludes with the presentation of a diagnosis of the State presence in these cities, in order to demonstrate how the regional public university, understood as an entity of the federal State, can contribute greatly to the training of agents of those communities in order to promote the development of their territories.